Prediction of mortality and major cardiovascular complications in type 2 diabetes: External validation of UK Prospective Diabetes Study outcomes model version 2 in two European observational cohorts. Issue 5 (22nd January 2021) - Pagano, Eva; Konings, Stefan R. A.; Di Cuonzo, Daniela; Rosato, Rosalba; Bruno, Graziella; van der Heijden, Amber A.; Beulens, Joline; Slieker, Roderick; Leal, Jose; Feenstra, Talitha L.
Abstract: Aim: To externally validate the UK Prospective Diabetes Study Outcomes Model version 2 (UKPDS‐OM2) by comparing the predicted and observed outcomes in two European population‐based cohorts of people with type 2 diabetes. Materials and methods: We used data from the Casale Monferrato Survey (CMS; n = 1931) and a subgroup of the Hoorn Diabetes Care System (DCS) cohort (n = 5188). The following outcomes were analysed: all‐cause mortality, myocardial infarction (MI), ischaemic heart disease (IHD), stroke, and congestive heart failure (CHF). Model performance was assessed by comparing predictions with observed cumulative incidences in each cohort during follow‐up. Results: All‐cause mortality was overestimated by the UKPDS‐OM2 in both the cohorts, with a bias of 0.05 in the CMS and 0.12 in the DCS at 10 years of follow‐up. For MI, predictions were consistently higher than observed incidence over the entire follow‐up in both cohorts (10 years bias 0.07 for CMS and 0.10 for DCS). The model performed well for stroke and IHD outcomes in both cohorts. CHF incidence was predicted well for the DCS (5 years bias −0.001), but underestimated for the CMS cohort. Conclusions: The UKPDS‐OM2 consistently overpredicted the risk of mortality and MI in both cohorts during follow‐up. Period effects may partially explain the differences. Results indicate that transferability is not satisfactory for all outcomes, and new or adjusted risk equations may be needed before applying the model to the Italian or Dutch settings.